Evaluation of Water Quality of Crown Golf Ornamental Lake, North Jakarta Based on N and P Content: Evaluasi Kualitas Air Danau Hias Crown Golf, Jakarta Utara Berdasarkan Kandungan N dan P - Widigdo, Bambang; Hariyadi, Sigid; Iswantari, Aliati; Pangaribuan, Adianto (Habitus Aquatica, 2020)
Anthropogenic activity surrounds the Crown Golf ornamental lake may contribute to waste input that could lead to the increasing of nutrient concentration and affect nutrient enrichment in the lake. This research aims to evaluate the water quality of Crown Golf ornamental lake, Pantai Indah Kapuk, North Jakarta based on N and P content. Water sampling was conducted for a year (September 2018 to August 2019) at four sampling locations. The main observed parameters were N (total nitrogen, ammonia, nitrite, nitrate) and P (total phosphate, orthophosphate). The data were analyzed for comparison of observed water quality and standard (Government Decree of Indonesia Republic No 82 the Year 2001), determination of N/P ratio, and determination of pollution level determination using Water Quality Index (WQI) and Pollution Index (IP) based on N and P content. The nutrient concentrations (nitrite, nitrate, and orthophosphate) were lower in the rainy season than in the dry season, while ammonia, total nitrogen, and total phosphate were not different between both seasons. Generally, the water quality of Crown Golf ornamental lake was still meet the standard for recreational activity (Class II). However, the obtained N/P ratio was very high (51:1). The pollution level of this lake is also moderate to bad (based on WQI) and slightly polluted to highly polluted (based on PI). This revealed that the Crown Golf ornamental lake had quite high N and P concentration and potentially causing the decrease of water quality and ecological function.